(untitled) (FULafia Journal of Science and Technology, 2020)
Lack of appropriate technologies in the wood processing industries in Nigeria has resulted in lower productivity and poor lumber recovery while in-situ primary processing of timber with appropriate technologies has not been well established to remedy this situation. This study assess the volume lumber recovery efficiency and waste generated in conventional, portable and artisanal sawmills in two selected locations within Southwestern Nigeria with a view to finding an alternative to this situation. Logs of about 11.34m3 volume were randomly selected and data were collected on the output/volume recovery and waste generated in each of the processing method. Data collected on the waste generated was partitioned in to sawdust and slab. ANOVA was used to analyze the data and mean separation was done using Duncan post hoc test